2012
DOI: 10.1016/j.bbamcr.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of mitochondrial dysregulation and resistance to mitochondrial-mediated apoptosis after genotoxic insult in normal human fibroblasts: A possible model for early stage carcinogenesis

Abstract: Acquisition of death-resistance is critical in the evolution of neoplasia. Our aim was to model the early stages of carcinogenesis by examining intracellular alterations in cells that have acquired apoptosis-resistance after exposure to a complex genotoxin. We previously generated sub-populations of BJ-hTERT human diploid fibroblasts, which have acquired death-resistance following exposure to hexavalent chromium [Cr(VI)], a broad-spectrum genotoxicant. Long-term exposure to certain forms of Cr(VI) is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Two death-resistant cell lines (DR1, DR2), as well as a death-susceptible clonogenic control line (CC1) were the focus of a recently published report from our laboratory (Nickens et al, 2012). Our data showed that, as compared to the death-susceptible cells, the DR cells were resistant to apoptosis as indicated by lack of cleaved caspase 3 expression following exposure to both Cr(VI) and cisplatin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two death-resistant cell lines (DR1, DR2), as well as a death-susceptible clonogenic control line (CC1) were the focus of a recently published report from our laboratory (Nickens et al, 2012). Our data showed that, as compared to the death-susceptible cells, the DR cells were resistant to apoptosis as indicated by lack of cleaved caspase 3 expression following exposure to both Cr(VI) and cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…Subclonal populations were derived as previously described (Nickens et al, 2012). The cell lines used in the present study include untreated clonogenic control cell lines, CC1 and CC2, as well as clones derived from clonogenic survivors of Cr(VI) exposure, DR1, DR2, DR3, and DR4, which display an apoptosis resistant phenotype.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations